Suppurative minor salivary gland sialolithiasis - Barbeiro, Camila de Oliveira [UNESP] (2022)
Sialolithiasis is a common nonneoplastic disease of the major salivary glands that often affects the submandibular glands. Minor salivary gland involvement by sialolithiasis is uncommon, with only 273 cases reported. A long clinical history, acute symptoms, and mucopurulent discharge are unusual features of these cases. Herein, we report the case of a 63-year-old woman who complained of symptomatic nodular swelling of the buccal mucosa associated with purulent discharge for several days. The clinical history lasted 15 years, with episodes of asymptomatic non-suppurative swelling in the same area. The patient underwent surgical excision. The microscopic examination revealed chronic nonspecific sialadenitis associated with psammomatous calcifications, confirming minor salivary gland sialolithiasis. After 3 years of follow-up, the patient was free of symptoms. Patients with sialolithiasis are usually asymptomatic; however, swelling, pain, and fistula may be present in rare cases. The presence of purulent exudate should lead to the differential diagnosis of stomatitis glandularis, a rare inflammatory condition affecting the minor salivary glands. Sialolithiasis and stomatitis glandularis should be considered in the clinical differential diagnosis of symptomatic suppurative nodular swelling affecting the oral mucosa, and histopathological analysis is necessary for the diagnosis.